1994
DOI: 10.1038/bjc.1994.342
|View full text |Cite
|
Sign up to set email alerts
|

The Edinburgh randomised trial of breast cancer screening: results after 10 years of follow-up

Abstract: MethodThe tria popukuion Detailed methods have been described previously (Roberts et al., 1984

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(46 citation statements)
references
References 17 publications
2
41
0
3
Order By: Relevance
“…Relative mortality figures from the Edinburgh and New York trials were not available, but it is known that the cases in non-attendees in these trials had survival rates close to those of the cases in the control groups. 13,14 It is therefore likely that the mortality reduction from screening lies somewhere between the uncorrected 38% and the bias-corrected 25%. This is consistent with the randomised trial results and suggests that the Breast Test Wales programme is achieving a similar quality to that of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…Relative mortality figures from the Edinburgh and New York trials were not available, but it is known that the cases in non-attendees in these trials had survival rates close to those of the cases in the control groups. 13,14 It is therefore likely that the mortality reduction from screening lies somewhere between the uncorrected 38% and the bias-corrected 25%. This is consistent with the randomised trial results and suggests that the Breast Test Wales programme is achieving a similar quality to that of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…On top of this, for the same cohort, at least another 200 women would go through the possible distress of a false-positive outcome. 16 Of the eight eligible trials in the Gotzsche and Nielsen review 16 (New York 1963, [17][18][19] Malmo 1976 [20][21][22] and Malmo II 1978, 23 Two-County 1977, [24][25][26] Edinburgh 1978, [27][28][29] Canada 1980, [30][31][32][33] Stockholm 1981, [34][35][36][37] Goteborg 1982 38,39 and UK Age Trial 1991 [40][41][42][43][44] ), one was excluded from meta-analysis because the randomisation was seriously flawed and the data held to be unreliable (Edinburgh 1978 28,29 ). Gotzsche and Nielsen 16 found that only three of the remaining trials had adequate randomisation.…”
Section: Discussionmentioning
confidence: 99%
“…This would represent a considerable public health benefit, comparable with the reduction in mortality shown by breast and colorectal cancer screening trials. [16][17][18][19] Secondary aims are to document the implementation of the screening programme; to determine its effectiveness in increasing participation in screening and in reducing the incidence of thick melanomas (thicker than 0.75 mm and thicker than 1.5 mm); and to determine the sensitivity, specificity, and costs of screening population for melanoma in the population by primary care physicians.…”
Section: Aims Of the Randomised Trialmentioning
confidence: 99%